Facilitated Transport of a Dpp/Scw Heterodimer by Sog/Tsg Leads to Robust Patterning of the Drosophila Blastoderm Embryo - Shimmi, Osamu (Cell, 2005)
Patterning the dorsal surface of the Drosophila blastoderm embryo requires Decapentaplegic (Dpp) and Screw (Scw), two BMP family members. Signaling by these ligands is regulated at the extracellular level by the BMP binding proteins Sog and Tsg. We demonstrate that Tsg and Sog play essential roles in transporting Dpp to the dorsal-most cells. Furthermore, we provide biochemical and genetic evidence that a heterodimer of Dpp and Scw, but not the Dpp homodimer, is the primary transported ligand and that the heterodimer signals synergistically through the two type I BMP receptors Tkv and Sax. We propose that the use of broadly distributed Dpp homodimers and spatially restricted Dpp/Scw heterodimers produces the biphasic signal that is responsible for specifying the two dorsal tissue types. Finally, we demonstrate mathematically that heterodimer levels can be less sensitive to changes in gene dosage than homodimers, thereby providing further selective advantage for using heterodimers as morphogens.